2012
DOI: 10.1111/mec.12110
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and dynamics predict mortality in a wild longitudinal study

Abstract: Explaining variation in life expectancy between individuals of the same age is fundamental to our understanding of population ecology and life history evolution. Variation in the length and rate of loss of the protective telomere chromosome caps has been linked to cellular lifespan. Yet, the extent to which telomere length and dynamics predict organismal lifespan in nature is still contentious. Using longitudinal samples taken from a closed population of Acrocephalus sechellensis (Seychelles warblers) studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
264
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(282 citation statements)
references
References 59 publications
12
264
6
Order By: Relevance
“…Critically short telomeres trigger a signal prompting the cell to permanently stop dividing, which leads to the induction of cellular senescence (Herbig et al, 2006). Furthermore, long telomeres have been found to correlate with good health and higher life expectancies in several species, thereby also serving as an indicator of somatic fitness, which represents the boundary of aging diseases (Bize et al, 2009;Horn et al, 2010;Barrett et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Critically short telomeres trigger a signal prompting the cell to permanently stop dividing, which leads to the induction of cellular senescence (Herbig et al, 2006). Furthermore, long telomeres have been found to correlate with good health and higher life expectancies in several species, thereby also serving as an indicator of somatic fitness, which represents the boundary of aging diseases (Bize et al, 2009;Horn et al, 2010;Barrett et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Short telomeres are strongly associated with cellular senescence, shortened lifespan, and reduced future reproductive success (20). Although long telomeres are maintained in the germ line through replenishment during meiosis, there is some evidence that telomere length is heritable and that such inheritance is sex specific (21)(22)(23) in birds, potentially resulting in daughters of older mothers having shorter telomeres (24)(25)(26), and, in turn, reduced fitness (27). The cellular consequences of aging and stress are similar, because both lead to oxidative damage that causes telomeres to shorten (20,28).…”
Section: Significancementioning
confidence: 99%
“…Telomeres appear to shorten throughout the life of individuals (Pauliny et al 2006;Bize et al 2009;Salomons et al 2009;Heidinger et al 2012;Angelier et al 2013;Barrett et al 2013;Bauch et al 2013;Boonekamp et al 2014) and, importantly, telomere length (TL) has been shown to be a reliable predictor of survival under some circumstances (Haussmann et al 2005;Pauliny et al 2006;Bize et al 2009;Salomons et al 2009;Heidinger et al 2012;Angelier et al 2013;Barrett et al 2013) but not others (Pauliny et al 2006;Beaulieu et al 2011;Caprioli et al 2013;Boonekamp et al 2014). Therefore, specific attention has been paid to the determinants of TL in wild vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…During adulthood, different individuals experience different environmental conditions and this can result in variable rates of telomere shortening between individuals Salomons et al 2009;Angelier et al 2013;Barrett et al 2013). Importantly, and contrary to TL, body size does not change after the developmental phase since birds have determinate growth, suggesting that telomere dynamics will become independent of structural body size in adults.…”
Section: Introductionmentioning
confidence: 99%